Analisis Manajemen Risiko Keamanan Self-Service Technology Perbankan Syariah - Nurzaqiah, Neli; Ainulyaqin, MH; Achmad, LI; Edy, Sarwo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Self Service Technology (SST) is a technology that allows customers to make transactions or carry out services independently without depending on employees. In the banking world, the Self-Service Technology services that customers can use are Automatic Teller Machine (ATM), Mobile Banking and Internet banking services to make things easier customers. However, you must be aware of various risks or potential incidents that could occur when customers use SST services. This research aims to analyze the security risk management of Sharia Banking Self-Service Technology. This research method uses a qualitative approach with field study methods through interviews and documentation. The results of this research are that Bank BJB Syariah has implemented Self-Service Technology security risk management with various strategies to minimize the security risks of Sharia Banking Self-Service Technology.